Synthesis and Antibacterial Activity of 6-(5’-Substituted-2’-benzofuryl)-4-aryl-4H-2-oxopyrimidines - Jadhav, D.V.; Choudhari, J.R.; Patil, L.S.; Shinde, N.D. (Asian Journal of Chemistry, 2010)
Various 2-acetyl-5-substituted benzofurans and their subsequent transformation into benzofuran analogues of a, b, unsaturated ketenes by reaction with various 5-substituted-5-hydroxyl benzaldehydes have been synthesized. These benzofuran analogues of a, b, unsaturated ketones are further modified chemically into different nitrogen heterocyclic systems. In present studies, the synthesis of oxopyrimidines coupled with various benzofurans was reported. The structures of these compounds were established on the basis of elemental analysis and spectral studies. Screening of antibacterial activity of synthesized oxopyrimidines were also carried out by qualitative methods.